2023
DOI: 10.1007/s00417-023-06019-y
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of a low-cost, non-valved glaucoma drainage device using mitomycin-C: 1-year results

Abstract: Purpose To evaluate the indications, outcomes, and complications of the usage of Aurolab Aqueous Drainage Implant (AADI) using mitomycin-C. Methods A retrospective case series of patients who underwent AADI placement using mitomycin-C between April 2018 and June 2020 at Ain Shams University Hospitals, Cairo, Egypt. The data was extracted from the records of the patients with a minimum of 1 year of follow-up. Complete success was defined as IOP ≥ 5 mmHg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…53 The Paul glaucoma implant (Advanced Ophthalmic Innovations, Singapore, Republic of Singapore) is a newer medical-grade silicone implant designed with a smaller tube diameter (0.127-mm internal diameter and 0.467-mm external diameter) and a plate size of 342 mm 2 that shows good results in pediatric glaucoma patients and potentially reduces the risk of hypotony, tube erosion, and endothelial cell loss. 54…”
Section: Glaucoma Drainage Implantsmentioning
confidence: 99%
“…53 The Paul glaucoma implant (Advanced Ophthalmic Innovations, Singapore, Republic of Singapore) is a newer medical-grade silicone implant designed with a smaller tube diameter (0.127-mm internal diameter and 0.467-mm external diameter) and a plate size of 342 mm 2 that shows good results in pediatric glaucoma patients and potentially reduces the risk of hypotony, tube erosion, and endothelial cell loss. 54…”
Section: Glaucoma Drainage Implantsmentioning
confidence: 99%
“…Intraoperative MMC during tube-shunt surgery has shown mixed results, with some authors reporting beneficial effects[ 21 22 ] while others reported no benefits. [ 23 ] A randomized trial by Costa et al .…”
Section: Mitomycin Cmentioning
confidence: 99%